The effect of soybean tempeh and gembus tempeh on obesity parameters, blood glucose, and short-chain fatty acids - Sunarti Sunarti; Agustina LN Aminin; Banundari Rachmawati; Mohammad Sulchan (AcTion: Aceh Nutrition Journal, 2025)
Obesity contributes to hyperglycemia and metabolic dysfunction globally. Soybean and gembus tempeh, traditional Indonesian fermented foods, contain distinct dietary fiber compositions that may differentially influence metabolic outcomes through short-chain fatty acid (SCFA) production. However, comparative evidence regarding their metabolic effects is limited. This study aimed to compare the effects of soybean and gembus tempeh on obesity parameters, fasting blood glucose, and SCFA profiles in a rat model of hyperglycemic obesity. Methods: A randomized controlled pre–post trial was conducted at the Food and Nutrition Study Center, Universitas Gadjah Mada (April–June 2019). Forty-two rats were assigned to seven groups: normal, hyperglycemic-obese + AIN-93, AIN-93 + gembus tempeh, AIN-93 + soybean tempeh, high-fat high-fructose diet (HFFD), HFFD + gembus tempeh, and HFFD + soybean tempeh. The obesity index, fasting blood glucose, and SCFA concentrations were measured. Both types of tempeh significantly reduced the obesity index and fasting glucose levels in rats fed either the AIN-93 or HFFD diet, with greater reductions observed in the AIN-93 group (p < 0.001). Butyrate levels were significantly higher in the tempeh-supplemented groups than in the control group (p < 0.01), whereas propionate levels did not differ significantly (p = 0.079). In conclusion, soybean tempeh and gembus tempeh improved fasting glucose levels, obesity index, and SCFA production in hyperglycemic-obese rats. Gembus tempeh demonstrated a greater effect on reducing obesity index and fasting blood glucose than soybean tempeh.